Characterization of the platelet-activating factor acetylhydrolase from human plasma by heterologous expression in Xenopus laevis oocytes. - Yamada, Y (1994)
Platelet-activating factor (PAF) has been implicated as a mediator of inflammation and atherosclerosis. A specific degradative enzyme found in plasma, PAF acetylhydrolase, plays important roles in various pathophysiological events induced by PAF. Human macrophages and Hep G2 cells secrete PAF acetylhydrolase with characteristics identical to the plasma activity. Other investigators reported that apolipoprotein B may possess phospholipase A2 activity, which suggested that apolipoprotein B might be a zymogen for PAF acetylhydrolase. However, while macrophages express PAF acetylhydrolase activity, we did not detect cDNAs for apolipoprotein B in a cDNA library from these cells, indicating that macrophages do not express this protein. In contrast, Hep G2 cells had high levels of cDNA for apolipoprotein B, as expected. We next injected Xenopus laevis oocytes with poly(A)+ RNA extracted from cultured human macrophages and Hep G2 cells. Twenty-five to 50% of Xenopus oocytes injected with poly(A)+ RNA from macrophages or Hep G2 cells secreted a PAF acetylhydrolase activity (1.0-7.8 nmol/ml per h) that also utilized a synthetic oxidized phospholipid as substrate. The activity secreted by poly(A)+ RNA-injected oocytes associated with lipoproteins and transferred between the particles in a pH-dependent manner, much like the plasma activity. These experiments establish that the properties of the enzyme released from poly(A)+ RNA-injected oocytes are identical to those of the plasma form of PAF acetylhydrolase and that the activity detected is not the expression of a domain in apolipoprotein B.